Letter (copy) : Assistance - Tewson, Vincent
034-0101-001 Secretary. HVT/FC/EK/529. 3rd January, 1939. Mrs. Charlotte Haldane, The International Brigade Dependants and Wounded Aid Committee, 1, Litchfield Street, London, W.C.2. Dear Mrs. Haldane, ASSISTANCE. In view of the time which has elapsed since your letter of September 12th, and although we have not received full particulars in regard to the number of Trade Unionists for whom your Committee is catering, the opportunity arose at the last meeting of the General Council to rise your request for assistance. The General Council were aware, of course, of the wide-spread nature of your appeal and also the fact that certain Unions have sent contributions. So far as the International Solidarity Fund is concerned, the monies donated for that purpose are specifically earmarked, and under all the circumstances it was decided that no action could be taken on the lines of your suggestion of September 12th. Yours sincerely, Assistant Secretary. 292/946/34/101